Preparation And Characterization Of Poly (Acrylate) Emulsion For Pour Point Depressant Application - Abd Razak, Ahmad Shaiful (2019)
Emulsion pour point depressant (PPD) is gaining extensive consideration in solving the solidification issue of conventional PPD at lower temperature. By producing PPD emulsion via polymerization system, low-temperature flow ability of PPD can be achieved. The main objective of this study is to establishing the correlation between process parameter and particles properties towards stability and performance of emulsion poly (acrylate) PPD. This study considered the effects of monomer loading towards various outputs, i.e. molecular weight, particle size, physicochemical, performance and the correlation between monomer loading and storage condition on the emulsion stability. Two type of acrylate monomer were used, methacrylate (MA) and methylmethacrylate (MMA) respectively. The monomer loading of the prepared acrylate emulsion were varied from 10 wt. % to 30 wt. %, respectively. PPD samples were characterized using Fourier Transform Infrared Spectroscopy (FTIR) and Gel Permeation Chromatography (GPC) unit. The performance of the PPD samples were evaluated by taking measurements of the pour point, physicochemical, thermal, zeta potential and particle size measurement. The increment of monomer loading resulted in a higher average molecular weight up to an optimum monomer loading of 20 wt.%. The value of the highest molecular weight, obtained was 4.09 x 107 g/mol for methyl methacrylate emulsion of 20 wt. % monomer loading. The particle size of the both emulsion poly (acrylate) PPD samples shows increment trends under the influence of monomer loading. The smallest particle size obtained was 64nm for sample methacrylate emulsion (10 wt.ix